2012
DOI: 10.1016/j.ntt.2012.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal exposure to sodium arsenite on motor and food-motivated behaviors from birth to adulthood in C57BL6/J mice

Abstract: Consumption of arsenic-contaminated drinking water is associated with numerous cancers and dermal and vascular diseases. Arsenic is also a potent nervous system toxicant and epidemiological studies indicate that intellectual functions in children are compromised following early developmental exposure. This study was designed to examine the effects of arsenic on a broad range of age-specific behaviors including basic sensory-motor responses in neonates, locomotor activity and grip strength in juveniles, and ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 55 publications
3
11
0
Order By: Relevance
“…In addition, several studies examining the relationship between iAs exposure and neurodevelopment in children showed reduced intellectual function and decreased learning ability, attention, and memory (Wasserman, 2007; Rosado, 2007; Dakeishi, 2006). A range of behavioral and cognitive impairments in the offspring of C57BL6/J mice prenatally exposed to iAs has been recently reported (Markowski, 2012). These data demonstrate the need for further investigation of arsenic as neurotoxic agent and its interactions with nutrient(s).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies examining the relationship between iAs exposure and neurodevelopment in children showed reduced intellectual function and decreased learning ability, attention, and memory (Wasserman, 2007; Rosado, 2007; Dakeishi, 2006). A range of behavioral and cognitive impairments in the offspring of C57BL6/J mice prenatally exposed to iAs has been recently reported (Markowski, 2012). These data demonstrate the need for further investigation of arsenic as neurotoxic agent and its interactions with nutrient(s).…”
Section: Discussionmentioning
confidence: 99%
“…Besides CNS manifestations, peripheral neuropathy is frequently reported in arsenic exposed individuals (Mathew et al, 2010;Barton and McLean, 2013) and has been linked with abnormal gait in exposed offsprings in experimental studies (García-Chávez et al, 2007). While a number of studies have found that arsenic exposure may affect the motor activity, consistent changes have not been observed as arsenic may cause both hyper and hypo-activity (Rodriguez et al, 2002(Rodriguez et al, , 2010Bardullas et al, 2009;Markowski et al, 2012). Differential changes in the motor activity following arsenic exposure have been suggested due to variation in the doses of arsenic, duration and route of exposure.…”
Section: Pd60 Pd90mentioning
confidence: 99%
“…In a letter in response to our paper, Williams and DeSesso questioned why a significant weight gain in arsenic (As)-exposed offspring was found in our study but not in others ( Markowski et al 2011 ; Markowski et al 2012 ; Tokar et al 2010 ; Waalkes et al 2003 ; Waalkes et al 2004 ; Waalkes et al 2006 ). In addition, they point out that early onset of vaginal opening in response to gestational As exposure was not observed by Markowski et al (2012) or Gandhi et al (2012) . As we mentioned in the Discussion section of our paper, some of the results under our exposure scheme do not recapitulate those observed in other studies.…”
mentioning
confidence: 53%